G6PD Deficiency. Global Distribution, Genetic Variants and Primaquine Therapy - Howes, R; Battle, K; Satyagraha, A; Baird, J; Hay, S (2013)
Glucose-6-phosphate dehydrogenase (G6PD) is a potentially pathogenic inherited enzyme abnormality and, similar to other human red blood cell polymorphisms, is particularly prevalent in historically malaria endemic countries. The spatial extent of Plasmodium vivax malaria overlaps widely with that of G6PD deficiency; unfortunately the only drug licensed for the radical cure and relapse prevention of P. vivax, primaquine, can trigger severe haemolytic anaemia in G6PD deficient individuals. This chapter reviews the past and current data on this unique pharmacogenetic association, which is becoming increasingly important as several nations now consider strategies to eliminate malaria transmission rather than control its clinical burden. G6PD deficiency is a highly variable disorder, in terms of spatial heterogeneity in prevalence and molecular variants, as well as its interactions with P. vivax and primaquine. Consideration of factors including aspects of basic physiology, diagnosis, and clinical triggers of primaquine-induced haemolysis is required to assess the risks and benefits of applying primaquine in various geographic and demographic settings. Given that haemolytically toxic antirelapse drugs will likely be the only therapeutic options for the coming decade, it is clear that we need to understand in depth G6PD deficiency and. primaquine-induced haemolysis to determine safe and effective therapeutic strategies to overcome this hurdle and achieve malaria elimination. © 2013 Elsevier Ltd.